Endometrial Hyperplasia Possibilities of Diagnostic Clarification - A. Levakov, Sergey; A. Sheshukova, Nataliya; A. Obukhova, Elizaveta (International Journal of Psychosocial Rehabilitation, 2020)
The present article is dedicated to the evaluation of histological and immunohistochemical methods in the differential diagnostics of endometrial hyperplasia and its association with chronic endometritis. The study included 350 patients aged 45–55 years old. The study entry criteria included abnormal uterine bleeding (85.6%) and/or the presence of sonographic signs of pathological changes in the endometrium (14.4%). Patients underwent endometrial curettage and hysteroscopy with histological examination of endocervical and uterine scrapings. By the results of histological examination, 2 groups were formed: the group of comparison (30 patients) included patients that did not have pathological alterations in the endometrium by the results of the morphological examination, and the main group (320 patients) included histologically confirmed endometrial hyperplasia. Further, immunohistochemical examination of the obtained endometrial tissue was performed. It was established that it is not always possible to diagnose chronic endometritis with the histological method. This method does not differentiate reactive hyperplasia from benign endometrial hyperplasia. For differential diagnostics of endometrial hyperplasia and its association with chronic endometritis, it is necessary to apply the immunohistochemical method, which will allow for the proper choice of the treatment tactics.